How to solve the differential equation ( d y <mrow class="MJX-TeXAtom-ORD"> / <

Cristopher Knox 2022-07-04 Answered
How to solve the differential equation ( d y / d x ) 2 = ( x y ) 2 with initial condition y ( 0 ) = 0?
I solved the equation by partitioning it into two differential equations.
1) d y / d x = x y The solution is 1 x + y = exp ( x )
and
2) 1 + x y = exp ( x )
How do we write combined solution of such equations.
You can still ask an expert for help

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Solve your problem for the price of one coffee

  • Available 24/7
  • Math expert for every subject
  • Pay only if we can solve it
Ask Question

Answers (1)

Allison Pena
Answered 2022-07-05 Author has 14 answers
y + y = x y = x 1 + K e x
Don't forget the constant of integration
y y = x y ( x ) = x + 1 + K e x
Did you like this example?
Subscribe for all access

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

You might be interested in

asked 2022-09-16
How to you find the general solution of 1 - 4 x 2 y = x ?
asked 2022-02-15
Find f(x) that satisfies the first-order differential equation:
f(sin2x)=cos2x+tan2x  (for 0<x<1)
Thanks!
asked 2022-06-25
I am currently doing a project about Growth and have found this really interesting Math Model by Dr. Geoffrey West et al in 2001 while researching.
I was wondering how does one integrate the differential equation
d m d t = a m 0.75 [ 1 ( m M ) 0.25 ]
where m is a function in terms of t and a, M are constants.
The end result (the integrated expression):
( m M ) 0.25 = 1 [ 1 ( m 0 M ) 0.25 ] e a t / ( 4 M 0.75 )
where m 0 is another constant (in the context of the problem, the initial mass of organism when t = 0).
I have tried solving by the integrating factors method but I couldn't express it in the form given... Anyone has any ideas?
asked 2022-09-14
What is a general solution to the differential equation y + 2 x y = 2 x 3 ?
asked 2022-06-24
I was given the following second-order differential equation,
y + 2 y + y = g ( t ) ,
and that the solution is y ( t ) = ( 1 + t ) ( 1 + e t ). Using the solution I determined that
g ( t ) = t + 3.
Following from this I transformed this second-order differential equation into a system of first-order differential equations, which is
( x 1 x 2 ) = ( 0 1 1 2 ) ( y y ) + ( 0 t + 3 )
Now I want to perform a single step with Δ t = 1 starting from t=0 with the Forward Euler method and after that with the Backward Euler method. Firstly with the Forward Euler method I use:
w n + 1 = w n + Δ t f ( t n , w n )
and I compute w 0 as
w 0 = ( y ( 0 ) y ( 0 ) ) = ( 2 1 )
so therefore
w 1 = ( 3 0 )
Now I want to perform the Backward Euler method.
w n + 1 = w n + Δ t f ( t n + 1 , w n + 1 )
so
w 1 = ( 2 1 ) + ( 0 1 1 2 ) w 1 + ( 0 4 )
From which i get
w 1 = 1 4 ( 11 3 )
y two results seems to be quite differnt and that gets me to believe that I have made a mistake somewhere. Could someone let me know if they believe this to be correct, or why this could be wrong?
asked 2021-01-02

Solve the Differential equations
(d2y)dt2+4dydt+3y=et

asked 2022-09-12
What is a general solution to the differential equation 1 + y 2 - y 1 - x 2 = 0 ?